Kecanduan Gadget dan Motivasi Belajar Siswa SMA: Implikasi bagi Layanan Bimbingan dan Konseling Islam - Neng Sinta Fatimah; M Fahli Zatrahadi; Miftahuddin (Yayasan pendidikan dzurriyatul Quran, 2026)
The rapid advancement of digital technology has led to a dramatic surge in mobile device use among young people, particularly high school students, which risks causing addiction and affecting their motivation to learn. This study aims to uncover the impact of mobile device addiction on high school students’ learning motivation, evaluate the contribution of Islamic Guidance and Counseling (BKI) services in addressing this addiction, and outline implications for improving students’ learning motivation. This study employs a qualitative method through a systematic literature review (SLR) of 15 scientific articles published between 2020 and 2025, sourced from the Google Scholar database. Key findings indicate a negative correlation between smartphone addiction and student learning motivation, although some evidence suggests the potential benefits of smartphones when used appropriately. BKI service techniques, such as group counseling, self-control, and cognitive therapy grounded in Islamic values, have proven effective in reducing smartphone addiction. Structured BKI services supported by collaboration between schools and families have a positive impact on restoring students’ learning motivation. The BKI approach provides a foundation for holistic interventions to balance technological proficiency with the academic achievement of high school students.